An innovative educational approach in using instructional videos to teach dental local anaesthetic skills. (1st August 2018) - Wong, Grace; Apthorpe, Heather C.; Ruiz, Kate; Nanayakkara, Shanika
Abstract: Objective: Good clinical skills are crucial for all dental practitioners. The transfer of knowledge from didactic lectures to daily clinical application can be challenging for current millennial learners. This study aimed to evaluate the effectiveness of using instructional videos to teach dental local anaesthesia in an undergraduate oral health programme in 2017. Methods: The philosophical basis of this study relies on the Advanced Trauma Life Support (ATLS) course which has been proven effective in practical education. Video clips were made in 3 different formats, with the addition of a quiz‐embedded version to reinforce learning and revision for practical assessments. Results: All the students agreed that their motivation to watch the videos was to refresh their memories before assessments. 90% of students agreed the videos helped them to learn psychomotor skills that required accuracy. There was a statistically significant correlation between the number of views of the videos on the administration of block injections and the marks received for practical assessment ( r  = 0.36, P  = 0.05), and correlation between participating in online quizzes and theory assessment ( r  = 0.371, P  = 0.044). Videos with narration and background music were found to be popular amongst oral health students. Conclusion: The use of instructional videos has been found effective in complementing the ATLS approach for teaching psychomotor skills in the administration of local anaesthetics by oral health students. Further studies are required to measure the students' retention of knowledge and application of skills on a patient in clinical settings.